High-performance perovskite solar cells fabricated by vapor deposition with optimized PbI2 precursor films. Issue 116 (6th November 2015) - Peng, Yanke; Jing, Gaoshan; Cui, Tianhong
Abstract : High-performance CH3 NH3 PbI3 solar cells were achieved by hybrid physical–chemical vapor deposition (HPCVD) method with optimized spin coating process for PbI2 precursor films. Abstract : The quality of a perovskite film determines the performance of a perovskite solar cell. A novel hybrid physical-chemical vapor deposition (HPCVD) method is presented to grow high-quality CH3 NH3 PbI3 films. These films were synthesized in a vacuum quartz tube with a constant growth temperature of 100 °C, resulting in the uniform film with grain sizes up to 800 nm and surface roughness of about RMS 17.4 nm. Combined with an optimized spin-coating process for PbI2 precursor films, a high-performance CH3 NH3 PbI3 solar cell's power conversion efficiency (PCE) can reach up to 14.2%. When treated in a controlled harsh environment at 80 °C for 96 hours, ten solar cells maintained 78% of their initial efficiency on average, which demonstrates the effectiveness of this HPCVD method.